Electron Affinity Control of Amorphous Oxide Semiconductors and Its Applicability to Organic Electronics. Issue 23 (4th October 2018) - Kim, Junghwan; Yamamoto, Koji; Iimura, Soshi; Ueda, Shigenori; Hosono, Hideo
Abstract: Energy level matching is a key factor for realizing efficient optoelectronics, such as organic light‐emitting diodes (OLEDs). Transition metal oxides (TMOs) are widely used as hole‐injection layers (HILs) because of their large electron affinities, corresponding to conduction band minimum levels ( E CBM ). However, the poor electrical properties and chemical instabilities of TMOs restrict device performance and fabrication processes. Conversely, amorphous oxide semiconductors (AOSs) exhibit superior electrical properties and chemical stability but cannot be applied to HILs because of their small electron affinities. In this study, a novel method is proposed to tune the electron affinity of conventional AOSs and an example material design of AOSs for HILs. The electron affinity deepening phenomenon that is attributable to the higher oxidation states of transition metal cations achieves a very deep E CBM of 5.7 eV for the proposed amorphous In–Mo–O (a‐IMO). Furthermore, an a‐IMO exhibits a high mobility of ≈1 cm 2 V −1 s −1 and high chemical stability against various solvents. As a result, it is demonstrated that a very thick a‐IMO layer is applicable to OLEDs as an HIL with no operating‐voltage increase. This study provides a new approach for efficient organic optoelectronics by tuning the electron affinity of AOSs. Abstract : A novel method is proposed to tune the electron affinity of conventional amorphous oxide semiconductors (AOSs) and an example material design of AOSs for hole‐injection layers (HILs). a‐In–Mo–O (In/Mo = 3/1) exhibits excellent properties for HILs: a rather deep E CBM of 5.7 eV, a high mobility of ≈1 cm 2 V −1 s −1 compared with MoO x, and high chemical stability against various solvents. As a result, an organic light‐emitting diode (OLED) using a 100 nm thick a‐In–Mo–O as an HIL exhibits a significantly lower operating voltage than an OLED using a 100 nm thick MoO x, particularly in the high luminance region.